49.5k views
4 votes
Solve

y=3x + 5


Equation 1: 3x+y=53x+y=5

Equation 2: 5x-4y=-35x−4y=−3 These equations for that question down below



Now that we've solved for y in Equation 1, it's time to substitute the resulting expression into Equation 2.


What will Equation 2 look like when we substitute correctly.

1 Answer

1 vote

Answer:

x=1, y=2. (1, 2).

Explanation:

3x+y=5

5x-4y=-3

--------------

y=5-3x

5x-4(5-3x)=-3

5x-20+12x=-3

17x-20=-3

17x=-3+20

17x=17

x=17/17=1

y=5-3(1)=5-3=2

x=1, y=2.

User Xxxvodnikxxx
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.